Language and the female body. - Nur Hidayah Abu Mansor. (2012)
The paper addresses the effects of the language used by men on women and the ways in which language as used by men oppresses and objectifies women by focusing on the female body. It will also look at the colonial implications of language and how it is used to create and contain the native female body, and how it can be adapted as a tool of colonial power. Focusing primarily on Graham Greene’s The Quiet American, the paper explores the relationship between language and culture, and how each creates or breaks down the sense of autonomy for the female body –both linguistically and physically - and also the consequences of this linguistic domination as a form indirect colonisation on the physical female body.The masculine language used on the female body defines and situates the woman in her gendered body. The impediment of linguistic development eventually leads to her to seek other means of communication and drives her, eventually, to utilize the same body –but in different ways –as a source of interaction. The essay also discusses Joseph Conrad’s Heart of Darkness and how Marlow, through the clever manipulation of language, is able to create or break down the sense of autonomy for the female body and simultaneously establish this same masculine superiority by imposing on the women an alleged inferiority. Finally, through Alice Walker’s The Color Purple, the essay argues that while the use of language enables and reinforces masculine domination, this same language can be manipulated and appropriated to the female use and thus break the hold that the men have on the women.